Design of a Half-Mode Substrate-Integrated Waveguide (HMSIW) Multimode Resonator Bandpass Filter Using the Minkowski Fractal for C-Band Applications - Muchhal, Nitin; Kumar, Abhay; Tewari, Nidhi; Kalia, Samriti; Srivastava, Shweta (Micromachines (Basel), 2024)
A substrate-integrated waveguide (SIW) bandpass filter (BPF) with extraordinary selectivity and an adequate upper stopband for C-band Satellite Communication (SATCOM) applications is proposed in this paper. The design comprises comb-shaped slots engraved on a half-mode SIW (HMSIW) that constitute a multimode resonator (MMR). Its performance is further ameliorated by applying the first and second iterations of the Minkowski fractal curve in the ground plane as a defected ground structure (DGS). The Minkowski fractal has advantages in terms of better bandwidth and miniaturization. The filter is first simulated using the commercial full-wave electromagnetic simulator HFSS v19 and then fabricated on a 0.062′′ (1.6 mm) FR4 with dielectric constant εr = 4.4. The measured results are comparable with the simulated ones and demonstrate that the BPF has a resonant frequency (f0) of 4.75 GHz, a 3 dB bandwidth of 770 MHz (fractional bandwidth of 21.4%), an insertion loss of 1.05 dB, and an out-of-band rejection (in the stopband) of more than 28 dB up to 8 GHz, demonstrating a wide and deep stopband. Using the multimode resonator (MMR) technique, a wide bandwidth has been achieved, and by virtue of using half-mode SIW (HMSIW), the proposed BPF is compact in size. Also, the fractal DGS aids in better stopband performance.